Toward a theory of motivational interviewing - Miller, William R; Rose, Gary S (The American psychologist, 2009)
The widely disseminated clinical method of motivational interviewing (MI) arose through a convergence of science and practice. Beyond a large base of clinical trials, advances have been made toward "looking under the hood" of MI to understand the underlying mechanisms by which it affects behavior change. Such specification of outcome-relevant aspects of practice is vital to theory development and can inform both treatment delivery and clinical training. An emergent theory of MI is proposed that emphasizes two specific active components: a relational component focused on empathy and the interpersonal spirit of MI, and a technical component involving the differential evocation and reinforcement of client change talk. A resulting causal chain model links therapist training, therapist and client responses during treatment sessions, and posttreatment outcomes.